2021
DOI: 10.21037/qims-20-768
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of 18F-fluorodeoxyglucose metabolic spatial distribution improves the differential diagnosis of indeterminate pulmonary nodules and masses with high fluorodeoxyglucose uptake

Abstract: Background: The aim of this study was to investigate the value of visual assessment of 18 F-fluorodeoxyglucose ( 18 F-FDG) metabolic spatial distribution (V-FMSD) in the diagnosis of indeterminate pulmonary nodules and masses with high 18 F-FDG uptake.Methods: A total of 301 patients with indeterminate pulmonary nodules or masses who underwent 18 F-FDG positron emission tomography/computed tomography (PET/CT) imaging were retrospectively studied. The characteristics of 18 F-FDG metabolic spatial distribution (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
2
2
0
Order By: Relevance
“…The FMSD in the proximal region of malignant lesions was significantly higher than that of the distal region, and the FMSD in the proximal region of benign lesions was significantly lower than that of the distal region. The sensitivity, specificity, PPV, NPV, and diagnostic accuracy of FMSD were 92.8%, 72.9%, 85.7%, 86.1%, and 89.2% ( 19 ), which is very similar to our research and further supports our conclusion, but diagnostic accuracy of combining PET/CT features with FMSD, and the optimal size of lesion for FMSD application was not discussed in their study. In our study, there were 29 patients whose lesions did not show the heterogeneity of 18 F-FDG uptake.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The FMSD in the proximal region of malignant lesions was significantly higher than that of the distal region, and the FMSD in the proximal region of benign lesions was significantly lower than that of the distal region. The sensitivity, specificity, PPV, NPV, and diagnostic accuracy of FMSD were 92.8%, 72.9%, 85.7%, 86.1%, and 89.2% ( 19 ), which is very similar to our research and further supports our conclusion, but diagnostic accuracy of combining PET/CT features with FMSD, and the optimal size of lesion for FMSD application was not discussed in their study. In our study, there were 29 patients whose lesions did not show the heterogeneity of 18 F-FDG uptake.…”
Section: Discussionsupporting
confidence: 87%
“…In the malignant lesions, blood supply from the bronchial artery was more abundant, causing the tumor cells in the proximal growing and metabolizing actively, and 18 F-FDG uptake was increased (21). However, chronic inflammation is more likely to stimulate the blood supply of extrapulmonary systemic circulation arteries, which are mostly located at the distal end of the heart (19). Therefore, the exudation of inflammatory lesions is more frequent at the distal end, leading to the high 18 F-FDG uptake in this location.…”
Section: Figurementioning
confidence: 99%
“…Our previous study has shown that the metabolic distribution of 2-[ 18 F]FDG in malignant nodules was different from that of benign ones (10). Generally, the 2-[ 18 F] FDG uptake in the proximal region of malignant lesion was higher than that in the distal region, which was also proved by our visual assessment of the spatial distribution of 2-[ 18 F] FDG metabolism (11). Although the visual method can be used as an auxiliary indicator to improve the diagnostic accuracy of pulmonary lesions with high 2-[ 18 F]FDG uptake, the analysis was a subjective empirical judgment method which may lead to subjective bias.…”
Section: Discussionsupporting
confidence: 72%
“…However, the acquisition of RAD requires complex diameter measurement and calculation, which limits its clinical application. Recently, we visually assessed the 2-[ 18 F]FDG spatial distribution in pulmonary lesions (11). Although this simple procedure could improve the diagnostic performance for hypermetabolic pulmonary nodules and masses, the main limitation lied in the subjective bias of observers, and the interobserver agreement needed to be further improved.…”
Section: Introductionmentioning
confidence: 99%